Pengaruh Pasca Accident/Incident Terhadap Beban Kerja Mental ATC di Perum LPPNPI Cabang Medan - Tri Saputra, Surya; Rizki Azizah, Luthfira; Sutama (Langit Biru: Jurnal Ilmiah Aviasi, 2023)
This research was aimed to examine the effect of ATC’s trauma after controlling an aircraft with an accident or incident on the ATC mental workload (Air Traffic Controller) at Perum LPPNPI Medan Branch. The analysis used an independent variable of trauma and the dependent variable is mental workload. The sample of this research is ATC who had ever controlled an aircraft. The method of this research is quantitative methods. The data analyzing in the forms of validity, reliability, normality, linearity, correlation, significance determination, and simple linear regression test. The result of this research with pearson product moment test showed the correlation is 0,8161 which categorized as very strong correlation and the determination shows 66,61%. The simple linear regression shows that every increase in the ATC’s trauma by one point will increase ATC’s mental-workload by 0.8312 at constant level of 2.4181.